Penyidikan Terhadap Pelaku Pencurian Benda Sitaan Pada Rumah Penyimpanan Benda Sitaan - Hattu, Tino Y S; Toule, Elsa Rina Maya; Wadjo, Hadibah Zachra (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The crime of theft that has occurred in state-owned warehouses is an important component in the criminal justice system, this is in accordance with the provisions of Article 44 of the Law of the Republic of Indonesia Number 8 of 1981 concerning the Criminal Procedure Code. . The theft that occurred at the Class I Rupbasan Ambon on April 22, 2020 is a form of criminal act. The criminal act of theft involved 3 (three) people as perpetrators, namely FD, NS, CN.Purposes of the Research: This writing aims to find out and discuss the process of investigating the theft of confiscated objects in Rupbasan. Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach and a conceptual approach and a case approach. The procedure for collecting legal materials uses library research, as well as processing and analyzing legal materials in this study using editing, systematization and description processing as well as qualitative analysis.Results of the Research: The results of this study explain that the process of investigating the crime of theft is the same as the process usually carried out by investigators for every criminal act. For the crime of theft at the Rupbasan, the investigation is carried out based on the provisions of Article 10 paragraph (1) of the National Police Chief Number 6 of 2019 concerning Criminal Investigation which is the basis for investigation activities, including (a) investigations; (b) commencement of the investigation; (c) coercive measures; (d) inspection; (e) determination of the suspect; (f) submission; (g) submission of case files; (h) surrender of the suspect and evidence. Functional coordination between investigators and Rupbasan against criminals, namely FD, NS and CN can be divided into 4 (four) sections, each of which includes: (a) Functional coordination in information on criminal acts of theft in Rupbasan; (b) Functional coordination in monitoring d; (c) Functional coordination in the case of criminal acts of theft at the Rupbasan; and (d) Functional coordination in securing evidence of theft from perpetrators.